The macro-metastasis/organ parenchyma interface (MMPI) - A hitherto unnoticed area. (February 2020) - Blazquez, R.; Sparrer, D.; Wendl, C.; Evert, M.; Riemenschneider, M.J.; Krahn, M.P.; Erez, N.; Proescholdt, M.; Pukrop, T.
Abstract: The macro-metastasis/organ parenchyma interface (MMPI) was previously considered an inert anatomical border which sharply separates the affected organ parenchyma from the macro-metastatic tissue. Recently, infiltrative growth of macro-metastases from various primary tumors was described in the brain, liver and lung, with significant impact on survival. Strikingly, the MMPI patterns differed between entities, so that at least nine different patterns were described. The MMPI patterns could be further classified into three major groups: displacing, epithelial and diffuse infiltrating. Additionally, macro-metastases are a source of further tumor cell dissemination in the affected organ; and these intra-organ metastatic dissemination tracks starting from the MMPI also vary depending on the anatomical structures of the colonized organ and influence disease outcome. In spite of their relevance, MMPIs and organ-specific dissemination tracks are still largely overlooked by many clinicians, pathologists and/or researchers. In this review, we aim to address this important issue and enhance our current understanding of the different MMPI patterns and dissemination tracks in the brain, liver and lung.